Effect of Glucose Addition on Physical Characteristics of Edible Film from Kappa-Carrageenan Using Sorbitol Plasticizer - Bestari, Nadia Gita; Saputra, Eka; Yuli Pujiastuti, Dwi (Journal of Marine and Coastal Science, 2024)
The development of increasingly advanced food technology has resulted in various new food product innovations, one example of which is edible film. Edible films can be made from polysaccharides such as kappa carrageenan with the addition of sorbitol and glucose plasticizers to improve their physical characteristics. This research aims to determine the effect of adding glucose on the physical properties of edible film from kappa carrageenan and sorbitol plasticizer. The research carried out was experimental using a Completely Randomized Design (CRD) with four treatments and five replications. Treatment consisted of glucose concentrations of 0%, 0.5%, 1%, and 1.5%. Data analysis used ANOVA, then continued with the DMRT test. The research results prove that glucose has a significant effect (p<0.05) on the physical characteristics of edible film. Optimal results were found at a glucose concentration of 0.5%, with a thickness value of 0.0972 mm, water vapor transmission rate of 3.319 g/m2/day, tensile strength of 3.2648 MPa, and elongation of 22.34%.